Suppression in any configuration : A versatile coupling improved multi-objective manipulation framework for modular active vibration isolation system. (1st March 2022) - Gong, Zhaopei; Ding, Liang; Xing, Hongjun; Gao, Haibo; Xu, Peng; Zhou, Ruyi; Lu, Yifan; Yue, Honghao
Abstract: Modular actuation units' development dramatically expands the compatibility and expandability of the modular active vibration isolation system (MAVIS) in space missions. However, due to the current shortness of a unified framework, manipulating such a redundantly actuated multi-input-multi-output (MIMO) nonlinear system assembled by modular units often involves painstaking challenges and repetitive trial. We proposed a unified coordinated manipulation and multi-objective vibration control framework with the ultimate goal of effectively vibration isolation for such systems. This framework, built on a general model and inherently coupling analysis, incorporates optimized manipulation with inversion system improved multi-objective control. Compared with the traditional multivariable feedback control, this framework effectively reduces the controller's order while ensuring the system's multiple objectives and frequency constraints. Experiments and simulations demonstrate the effectiveness of the proposed framework in achieving coordinated manipulation and vibration attenuation on a physical system and indicate the potential role of its application for a family of modular active vibration isolation systems. Highlights: For a family of modular isolation units, a standardized decoupling and vibration control framework with wide adaptability is proposed. An unified decoupling and coordination paradigm is set as pre-processing before control design. A control framework is proposed to balance the impact of different disturbances, and to achieve the unification of the contradictory goals between vibration suppression and collision avoidance. The decoupling and vibration suppression effect is experimentally verified on a six-DoF mount composed of modular isolation units. Experimental setups for mimicking low-gravity environment are built.